Masculinity and Femininity in the Qur’an: Reflections on the Personalities of the Prophet Muhammad and Siti Khadijah - Moh Soim; Zein Fuady; Muhammad Zahid (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
This study examines the reflection of masculinity and femininity in the Qur’an and its relationship to the personality of Prophet Muhammad and his beloved wife, Siti Khadijah, in providing role models for humanity. The method used in this study is qualitative. Data sources were obtained through a review of various journals, news articles, expert analyses, and related literature. Data analysis uses the interpretation of past and present scholars on verses related to the theme and opinions of scientists. This study focuses on the masculine and feminine traits in which many patriarchal societies view men as superior to women, even though this is not the case in teachings. Therefore, this study presents concrete evidence on the personalities of Prophet Muhammad and Siti Khadijah. The findings of this study include the definition of masculinity and femininity, the Islamic response to both, and the personalities of Prophet Muhammad and Siti Khadijah in practicing masculinity and feminism as a benchmark for humanity. This study concludes that men and women can possess masculine and feminine traits, in that women can have masculine characteristics and men can have feminine traits, provided that they are legitimized by Islamic law.